Global conceptual history a reader - Pernau, Margrit; Sachsenmaier, Dominic (London [u.a.] : Bloomsbury, 2016)
"The influential readings contained in this volume combine conceptual history - the history of words and languages - and global history, showing clearly how the two disciplines can benefit from a combined approach. The readings familiarize the reader with conceptual history and its relationship with global history, looking at transfers between nations and languages as well as the ways in which world-views are created and transported through language. Part One: Classical Texts presents the three foundational texts for conceptual history, giving the reader a grasp of the origins of the discipline. Part Two: Challenges focuses on critiques of the approach and explores their ongoing relevance today. Part Three: Translations of Concepts provides examples of conceptual history in practice, via case studies of historical research with a global scope. Finally, the book's concluding essay examines the current state and the future potential of conceptual history. This original introduction provides the students of conceptual, global and intellectual history with a firm grasp of the past trajectories of conceptual history as well as its more recent global and transnational tendencies, and the promises and challenges of writing global history" "The influential readings contained in this volume combine conceptual history - the history of words and languages - and global history, showing clearly how the two disciplines can benefit from a combined approach. The readings familiarize the reader with conceptual history and its relationship with global history, looking at transfers between nations and languages as well as the ways in which world-views are created and transported through language. Part One: Classical Texts presents the three foundational texts for conceptual history, giving the reader a grasp of the origins of the discipline. Part Two: Challenges focuses on critiques of the approach and explores their ongoing relevance today. Part Three: Translations of Concepts provides examples of conceptual history in practice, via case studies of historical research with a global scope. Finally, the book's concluding essay examines the current state and the future potential of conceptual history. This original introduction provides the students of conceptual, global and intellectual history with a firm grasp of the past trajectories of conceptual history as well as its more recent global and transnational tendencies, and the promises and challenges of writing global history"
Machine generated contents note: History of Concepts and Global History / Margrit Pernau (Max Planck Institute for Human Development, Berlin, Germany), Dominic Sachsenmaier (Jacobs University, Germany) -- Part One: Classical Texts in Conceptual History -- 1. Introduction (Einleitung) to the Geschichtliche Grundbegriffe / Reinhart Koselleck (University of Bielefeld, Germany) -- 2. Social History and Conceptual History / Reinhart Koselleck -- 3. For a Socio-historical Semantics as a Middle Course between 'Lexicometry' and 'Conceptual History' / Rolf Reichardt (University of Giessen, Germany) -- Part Two: Challenges -- 4. Conceptual History or a History of Discource? On the Theoretical Basis and Questions of Methodology of a Historical-Semantic Epistemology / Dietrich Busse (University of Düsseldorf, Germany) -- 5. Rhetoric and Conceptual Change / Quentin Skinner (Queen Mary, University of London, UK) -- Part Three: Translations of Concepts -- 6. Translation as Cultural Transfer and Semantic Interaction: European Variations of Liberal between 1800 and 1830 / Jörn Leonhard (University of Freiburg, Germany) -- 7. Translation, Politics and Conceptual Change / Kari Palonen (Academy of Finland) -- 8. The Question of Meaning-Value in the Political Economy of the Sign / Lydia H. Liu (Columbia University, USA) -- 9. The Resonance of Culture: Framing a Problem in Global Concept-History / Andrew Sartori (New York University, USA) -- 10. The Conceptualization of the Social in Late Nineteenth- and Early Twentieth-century Arabic Thought and Language / Ilham Makdisi (Northeastern University, USA)USD hIlham Makdisi (Northeastern University, USA) -- 11. Ustaarabu: A Conceptual Change in Tanganyikan Newspaper Discourse in the 1920s / Katrin Bromber (Center for Modern Oriental Studies, Berlin, Germany) -- 12. Pictures, Emotions, Conceptual Change: Anger in Popular Hindi Cinema / Imke Rajamani (Max Planck Institute for Human Development, Berlin, Germany) -- Part Four: Outlook -- 13. Forty Years of Conceptual History: The State of the Art / Willibald Steinmetz (University of Bielefeld, Germany).
Keywords: Begriffsgeschichte <Fach>; Historische Semantik; Linguistik; Globalisierung; Variation; Pädagogik; Historische Sprachwissenschaft; Weltgeschichte; Weltgeschichte; Begriffsgeschichte <Fach>; Aufsatzsammlung